Production Quotas as Bounds on Interplant JIT Contracts - Duenyas, Izak; Hopp, Wallace J.; Bassok, Yehuda (Management Science, 1997)
We consider the situation of a supplier plant whose customer plants desire just-in-time (JIT) deliveries. Randomness in both the production and demand processes make satisfying every demand that might occur in true JIT fashion impossible. Therefore, supplier plants typically negotiate bounds on JIT contracts with their customers. In this paper, we focus on the use of “quotas” or “target inventory levels” as a mechanism for establishing such bounds. That is, the supplier firm is responsible for meeting periodic demands up to the quota, but not beyond. In this paper, we consider the problem of setting an appropriate quota from the perspective of the supplier plant and interpret our results in the context of the negotiation process between the supplier and its customers. Under the assumption that “safety capacity” (i.e., overtime or a vendoring option) is available, we develop two models that address this problem. The first model assumes that quota shortfalls cannot be carried over to the next regular time production period and are made up with overtime/vendoring, which incurs fixed plus variable costs. The second model assumes that shortages can be backlogged to the next regular time production period at a cost. We use numerical examples to demonstrate how the models we developed were used by a clutch supplier to a large auto manufacturer to negotiate its JIT contracts.